Stock Market Reactions to India's 2016 Demonetization: Implications for Tax Evasion, Corruption, and Financial Constraints - Dhammika Dharmapala; Vikramaditya Khanna (Center for Economic Studies and ifo Institute (CESifo), 2017)
On November 8, 2016, the Indian government made a surprise announcement that certain currency notes (representing 86% of the currency then in circulation) would no longer be legal tender (although they could be deposited in banks over a limited period). The stated reason for this sudden “demonetization” was to combat tax evasion and corruption associated with “unaccounted-for” cash. We compute abnormal returns for firms on the Indian stock market around this event, and compare patterns of abnormal returns for different subsamples of firms defined by industry, ownership structure, and other characteristics. There is little evidence that sectors thought to be associated with greater tax evasion or corruption experienced significantly different returns. However, we find substantial positive returns for banks and for state owned enterprises (SOEs), implying market expectations that are puzzling in some respects, especially as the initial reactions do not show any evidence of reversal in the five months following the event. The bank results appear to indicate a market expectation of a persistent increase in financial depth. We also find a pattern of higher returns for industries that are characterized by a greater dependence on external finance, possibly suggesting an expectation of an easing of financial constraints. The returns for SOEs may be due to possible indirect effects of the announcement on perceptions of future corruption among these firms.
Keywords: E42; H26; 330; corruption; tax evasion; demonetization; financial constraints; India